Analysis of The Ina219 Sensor System And Voltage Divider On A Calibrate Multimeter: Fitri Puspasari, Trias Prima Satya - Fitri Puspasari Fitri Puspasari; Trias Prima Satya Trias Prima Satya (Jurnal Fisika dan Aplikasinya, 2024)
Research has been carried out on uncertainty studies in current and voltage measurements based on the Internet of Things using the NodeMCU ESP8266 microcontroller. This research aims to design a current and voltage or power meter using a current sensor in the form of an INA219 module and a voltage sensor with a microcontroller-based voltage divider circuit module and determine the validity of the measuring results of the instrument created. The method used in this research consists of three stages: hardware design, software design and system testing.